Clinical Relevance of New World Health Organization Classification System for Pituitary Adenomas: A Validation Study With 2-Year Experience - Hong, Seung Woo; Kim, Se Hoon; Lim, Seung Hoon; Lee, Eun Jig; Kim, Sun Ho; Ku, Cheol Ryong; Kim, Eui Hyun (Frontiers in Oncology, 2021)
Background: The new World Health Organization (WHO) classification system proposed a cell lineage-based classification scheme for pituitary adenomas in which transcription factors (TFs) play a major role as key classifiers. We aimed to evaluate clinical relevance of the new classification system in a clinical setting. Methods: TF staining was retrospectively performed for 153 clinically and histologically well characterized pituitary adenomas. Then, 484 pituitary adenomas were prospectively stained for TFs and then for relevant pituitary hormones. TF and hormone stain-based diagnoses were compared, and differences in clinical manifestations were evaluated. Results: The accuracies of antibodies for three TFs were successfully validated and had an overall matching rate was 89.6%. We identified 50 (10.4%) cases with discrepancies between TF and pituitary hormone stains. Gonadotroph adenomas lacking follicle-stimulating hormone and luteinizing hormone stains account for most discrepancies. Null cell adenomas may be more prevalent than reported and may be clinically more aggressive than gonadotroph adenomas. Conclusion: The new WHO classification is mostly well matched with the traditional classification. However, until the new classification is further validated and interpreted in the context of long-term clinical outcomes, routine histological examination should include full slate of immunostains for pituitary hormones as well as TFs.